Forced reconnection in the near magnetotail: Onset and energy conversion in PIC and MHD simulations. Issue 1 (28th January 2014) - Birn, J.; Hesse, M.
<x xml:space="preserve">Abstract</x> Using two‐dimensional particle‐in‐cell (PIC) together with magnetohydrodynamic (MHD) simulations of magnetotail dynamics, we investigate the evolution toward onset of reconnection and the subsequent energy transfer and conversion. In either case, reconnection onset is preceded by a driven phase, during which magnetic flux is added to the tail at the high‐latitude boundaries, followed by a relaxation phase, during which the configuration continues to respond to the driving. The boundary deformation leads to the formation of thin embedded current sheets, which are bifurcated in the near tail, converging to a single sheet farther out in the MHD simulations. The thin current sheets in the PIC simulation are carried by electrons and are associated with a strong perpendicular electrostatic field, which may provide a connection to parallel potentials and auroral arcs and an ionospheric signal even prior to the onset of reconnection. The PIC simulation very well satisfies integral entropy conservation (intrinsic to ideal MHD) during this phase, supporting ideal ballooning stability. Eventually, the current intensification leads to the onset of reconnection, the formation and ejection of a plasmoid, and a collapse of the inner tail. The earthward flow shows the characteristics of a dipolarization front: enhancement of Bz, associated with a thin vertical electron current sheet in the PIC simulation. Both MHD and PIC simulations show a dominance of energy conversion from incoming Poynting flux to outgoing enthalpy flux, resulting in heating of the inner tail. Localized Joule dissipation plays only a minor role.